2006
DOI: 10.1080/00498250600861728
|View full text |Cite
|
Sign up to set email alerts
|

Compendium of gene expression profiles comprising a baseline model of the human liver drug metabolism transcriptome

Abstract: Oligonucleotide microarrays were used to study the variability of pharmacokinetics and drug metabolism (PKDM)-related gene expression in 75 normal human livers. The objective was to define and use absorption, distribution, metabolism and excretion (ADME) gene expression variability to discern co-regulated genes and potential surrogate biomarkers of inducible gene expression. RNA was prepared from donor tissue and hybridized on Agilent microarrays against an RNA mass balanced pool from all donors. Clustering of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 26 publications
3
17
0
Order By: Relevance
“…In addition, Kawashima et al (2006) demonstrated binding of HNF4␣ to the CYP2C9 promoter with an immunoprecipitation from human liver. Although recent microarray data did not detect the same correlations between expression levels of HNF4␣ and target genes as the current study, this effect is likely accounted for by the low detection level of HNF4␣ by the microarray used (Slatter et al, 2006). HNF4␣ has been shown to exert a dose-dependent effect upon mRNA expression level of CYP2A6, CYP2B6, CYP2C9, CYP2D6, CYP3A4, and CYP3A5 in primary human hepatocytes when HNF4␣ expression was gradually reduced using antisense RNA (Jover et al, 2001).…”
Section: Regulation Of Drug Metabolism Gene Expressionmentioning
confidence: 42%
“…In addition, Kawashima et al (2006) demonstrated binding of HNF4␣ to the CYP2C9 promoter with an immunoprecipitation from human liver. Although recent microarray data did not detect the same correlations between expression levels of HNF4␣ and target genes as the current study, this effect is likely accounted for by the low detection level of HNF4␣ by the microarray used (Slatter et al, 2006). HNF4␣ has been shown to exert a dose-dependent effect upon mRNA expression level of CYP2A6, CYP2B6, CYP2C9, CYP2D6, CYP3A4, and CYP3A5 in primary human hepatocytes when HNF4␣ expression was gradually reduced using antisense RNA (Jover et al, 2001).…”
Section: Regulation Of Drug Metabolism Gene Expressionmentioning
confidence: 42%
“…Three of these genes-EHHADH, SLC10A1, and AKR1D1-were also found to be top hub genes in the P450-correlated turquoise module from the independent coexpression network. In the literature, EHHADH has been found to be responsive to ligands of AHR, NR1I3 (CAR), and NR1I2 (PXR); SLC10A1 is selectively responsive to AHR ligands; AKR1D1 is selectively responsive to PXR ligands (Slatter et al 2006). Thus, these three upstream genes represent novel putative key regulators of P450 genes.…”
Section: Genetics and Genomics Of Human Liver P450smentioning
confidence: 99%
“…We obtained consensus compound signatures in mouse and rat livers that are responsive to 26 inducers of AHR, NR1I3 (CAR), and NR1I2 (PXR) (e.g., AHR ligand flutamide, CAR ligand androstenol, and PXR ligand hyperforin) (Slatter et al 2006), and analyzed the overlap between these signatures and our network. Indeed, our P450 subnetwork is significantly enriched not only for mouse genes responsive to ligands of AHR, CAR, PXR, and all three receptors with enrichment P-values of 1.66 3 10 À12 , 1.08 3 10 À14 , 9.74 3 10 À13 , and 6.19 3 10…”
Section: Constructing a Predictive Bn From The Hlc Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in many cases the derived function is no better than a guess. Although true functional genomics studies have been done using complex experimental readouts from known physiological states or positive controls and pattern matching the resulting readouts, [1][2][3][4][5][6] RNAi allows for the first time the direct measurement of gene function in pathways of interest on a genome-wide scale. This approach has been quickly embraced in both academic and industrial research.…”
mentioning
confidence: 99%